Rooting for success: Evolutionary enhancement of Bacillus for superior plant colonization - Vincent Charron‐Lamoureux; Sandrine Lebel‐Beaucage; Maude Pomerleau; Pascale B. Beauregard (Microbial Biotechnology, 2024)
Abstract Many strains from the Bacillus subtilis species complex exert strong plant growth‐promoting activities. However, their efficacy in relevant conditions is variable, due in part to their inability to establish a strong interaction with roots in stressful environmental conditions. Adaptative laboratory evolution (ALE) is a powerful tool to generate novel strains with traits of interest. Many Bacillus evolved isolates, stemming from ALE performed with plants, possess a stronger root colonization capacity. An in‐depth analysis of these isolates also allowed the identification of key features influencing the interaction with plant roots. However, many variables can influence the outcome of these assays, and thus, caution should be taken when designing ALE destined to generate better root colonizers.